2015
DOI: 10.1111/iwj.12429
|View full text |Cite
|
Sign up to set email alerts
|

Comparing the Meggitt‐Wagner and the University of Texas wound classification systems for diabetic foot ulcers: inter‐observer analyses

Abstract: Accurate classification of diabetic foot ulcers is essential for inter-clinician communication, assessment of healing tendency and determination of treatment options. The aim of this study was to assess the inter-observer agreement (IOA) of the most commonly used classification systems for diabetic foot ulcers; the Meggitt-Wagner (MW) and the University of Texas (UT) systems. In this study, 95 clinicians judged digital photographs of diabetic foot ulcers in various stages of healing. Wound depth was classified… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
34
0
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(38 citation statements)
references
References 28 publications
1
34
0
3
Order By: Relevance
“…We have also noted the following limits and shortcomings: (a) lack of details about the exact kind, location, and extension of foot ulcers, and imaging examinations of the limb arterial axis were also not provided; (b) we could not examine the risk factors for major and minor amputations separately because of limited data; (c) medication used was not analysed in the present study, which might explain why these patients with comorbidities were less likely to undertake amputation; and (d) we only used the Wagner classification system, which provided little information about ulcer size and infection status. Other classification systems, such as the University of Texas (UT); the perfusion, extent, depth, infection, and sensation (PEDIS); and ulcer size (area and depth), sepsis, arteriopathy, and denervation (S[AD]SAD) systems, could provide more detailed information about the foot ulcer; (e) being a retrospective study and not involving long‐term outcome, a prospective multicentre research on a larger scale will be much more helpful for preventing amputations because of DFU.…”
Section: Discussionmentioning
confidence: 99%
“…We have also noted the following limits and shortcomings: (a) lack of details about the exact kind, location, and extension of foot ulcers, and imaging examinations of the limb arterial axis were also not provided; (b) we could not examine the risk factors for major and minor amputations separately because of limited data; (c) medication used was not analysed in the present study, which might explain why these patients with comorbidities were less likely to undertake amputation; and (d) we only used the Wagner classification system, which provided little information about ulcer size and infection status. Other classification systems, such as the University of Texas (UT); the perfusion, extent, depth, infection, and sensation (PEDIS); and ulcer size (area and depth), sepsis, arteriopathy, and denervation (S[AD]SAD) systems, could provide more detailed information about the foot ulcer; (e) being a retrospective study and not involving long‐term outcome, a prospective multicentre research on a larger scale will be much more helpful for preventing amputations because of DFU.…”
Section: Discussionmentioning
confidence: 99%
“…The ulcer location was determined by the vascular surgeon and wound consultant, respectively, at the first visit. The UT Classification categorises the ulcer by using, respectively, four grades and four stages with a scale from 0 through 3 including stages to clarify the presence of infection or ischemia (Supplementary Table 1, which demonstrates the UT Classification) …”
Section: Methodsmentioning
confidence: 99%
“…The UT Classification categorises the ulcer by using, respectively, four grades and four stages with a scale from 0 through 3 including stages to clarify the presence of infection or ischemia (Supplementary Table 1, which demonstrates the UT Classification). 17 Key Messages • diabetic foot ulcers (DFUs) are the most common and feared complication of diabetes • the aim of this study was to identify DFU patients at risk for the development of hard-to-heal wounds • the number of ulcers in history, University of Texas classification grade, and a diagnose of foot stand deformation were significantly associated with the development of a hard-to-heal wound • these patient characteristics can be used to identify patients at risk, who might need an early intervention to prevent wound problems…”
Section: Study Design and Populationmentioning
confidence: 99%
“…14 A more recent study comparing the UT and Meggitt-Wagner systems, using digital photographs of DFU, found only moderate agreement amongst the group of clinicians, and significantly higher agreement between nurses than doctors. 15 The wide variation in presentation, aetiology and outcomes of patients with DFU makes it difficult to select a single scoring system for widespread use, particularly as the prevalence of influencing factors, such as PAD, varies across the world and the factors most strongly associated with outcomes depend on the population studied. 16 In addition, whilst many of the wellknown systems have been internally validated, there is a lack of robust external validation for many scores, as well as poor reliability when used on a global scale by different types of health professionals.…”
Section: Discussionmentioning
confidence: 99%